TREATMENT OF METHADONE PATIENTS WITH NEUROLEPTIC THERAPY AND HYPERPORLACTINEMIA - Spasovska Trajanovska, Aneta; Janichevikj Ivanovska, Danijela (Scientific Institute of Management and Knowledge, 2024)
According to certain findings, heroin addiction represents a significant medical as well as social problem. It is known that with opioid substitution treatment this disease can be overcome or alleviated. However, the application of this treatment does not always give the expected results, so it is necessary to apply additional neuroleptic therapy until the patients are fully stabilized. But the joint application of substitution and neuroleptic therapy can lead to a series of side effects, one of which is the appearance of hyperpolactinemia.The aim of this study is to observe the prevalence of symptoms of hyperprolactinemia in patients with poor response to methadone treatment, treated with neuroleptic therapy.Material and methods: The cross-sectional study evaluated 20 male patients with a mean age of ±24.13 years treated at the Skopje Psychiatric Hospital with high doses of Sol methadone 80-120 mg/day. All patients had abad agreement on the methadone treatment, so additional therapy was included, tab. Risperidone with an average dose of 2 mg/day. Participants signed an informed consent to participate.Patients were assessed using a semi-structured questionnaire specifically designed for the study. Data consisted of age, sex, and symptoms of hyperprolactinemia: amenorrhea, loss of libido, erectile dysfunction, and gynecomastia. The results of this study were analyzed using descriptive methods, t-test and Pearson's correlation coefficient. The p value of statistical significance was set at p<0.05.Results: The results obtained in our study showed that a certain percentage of methadone patients who were on Risperidone therapy had symptoms of hyperprolactinemia, but the results were without statistical significance p>0.05.Conclusion: although in our study we obtained a small percentage of patients with symptoms of hyperprolactinemia, care must be taken in patients on methadone treatment who are also treated with neuroleptic therapy due to their synergistic effect, we should always keep in mind the possibility of developing hyperprolactinemia.
Keywords: methadone treatment patients; risperidone; hyperprolactinemia